2010
DOI: 10.1097/hp.0b013e3181bfa16b
|View full text |Cite
|
Sign up to set email alerts
|

CARCINOGENESIS FROM INHALED 239PuO2 IN BEAGLES: EVIDENCE FOR RADIATION HOMEOSTASIS AT LOW DOSES?

Abstract: From the early 1970's to the late 1980's, Pacific Northwest National Laboratory conducted life-span studies in beagle dogs on the biological effects of inhaled plutonium ((238)PuO(2), (239)PuO(2), and Pu[NO(3)](4)) to help predict risks associated with accidental intakes in workers. Years later, the purpose of the present follow-up study was to reassess the dose-response relationship for lung cancer in the PuO(2) dogs compared to controls-with particular focus on the dose-response at relatively low lung doses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…As evidenced by the results of experimental studies conducted in the in vivo and in vitro systems, one of the most important underlying mechanisms of such tumor-inhibitory effects is up-regulation of both the innate and adaptive immunity. Numerous reports published between 1988 and 2014 indicate that exposures to LLR are potent stimulators of various anti-neoplastic functions of the immune system, including inhibition of inflammation and/or up-regulation of anti-inflammatory cytokines (evidence presented in Supplementary Table 3 and reviewed in [74, 80, 94, 170, 171]).…”
Section: Anti-neoplastic and Immunomodulatory Effects Of Llrmentioning
confidence: 99%
“…As evidenced by the results of experimental studies conducted in the in vivo and in vitro systems, one of the most important underlying mechanisms of such tumor-inhibitory effects is up-regulation of both the innate and adaptive immunity. Numerous reports published between 1988 and 2014 indicate that exposures to LLR are potent stimulators of various anti-neoplastic functions of the immune system, including inhibition of inflammation and/or up-regulation of anti-inflammatory cytokines (evidence presented in Supplementary Table 3 and reviewed in [74, 80, 94, 170, 171]).…”
Section: Anti-neoplastic and Immunomodulatory Effects Of Llrmentioning
confidence: 99%
“…The appearance of the paper by Fisher and Weller (2010) triggered further thoughts on this topic by Simmons and Richards (Simmons and Richards 2012). They noted the fact that, in the paper by Muggenburg et al (2008), a plot of the incidence of lung tumors as a function of dose appears to show a threshold at approximately 1 Gy.…”
Section: Introductionmentioning
confidence: 99%
“…At about the same time, Fisher and Weller published the results of their lifespan studies of beagles that had inhaled both plutonium dioxide and plutonium nitrate (Fisher and Weller 2010). Following inhalation, initial lung burdens ranged from 130 Bq to 215 kBq.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of a study on inhaled 239 PuO 2 particles in beagle dogs, Fisher and Weller (2010) , identified the possibility of a beneficial health effect—lung tumor suppression at a low radiation dose. This was based on a statistical test they carried out “on the null hypothesis to determine the probability that the controls and the lowest dose groups have the same underlying probability of tumor incidence, and that tumor incidence is unrelated to dose (testing for a threshold effect).” Because of the infinitesimally small amount of plutonium in these studies, chemical toxicity does not need consideration.…”
Section: Introductionmentioning
confidence: 99%
“…For the lung tumor data (spontaneously-occurring plus radiation-induced) in Fig. 4 of Fisher and Weller (2010) , the LNT model would predict about 5 tumors in the 26 dogs that were exposed to a cumulative alpha-radiation dose in the range 8 to 48 cGy. The observed incidence of 0 tumors in the 16 dogs in the 8 to 22 cGy range and 1 tumor in the 10 dogs in the 27 to 48 cGy range suggests a beneficial effect, but the LNT statistical variations of these low tumor observations are too large to challenge the LNT prediction of 5 tumors.…”
Section: Introductionmentioning
confidence: 99%